Altered cerebral blood flow in the anterior cingulate cortex is associated with neuropathic pain. Issue 10 (7th April 2018) - Watanabe, Keisuke; Hirano, Shigeki; Kojima, Kazuho; Nagashima, Kengo; Mukai, Hiroki; Sato, Takatoshi; Takemoto, Minoru; Matsumoto, Koji; Iimori, Takashi; Isose, Sagiri; Omori, Shigeki; Shibuya, Kazumoto; et al.
Abstract : Objective: To assess the cerebral blood flow (CBF) in patients with diabetic neuropathic pain, and its changes after duloxetine therapy. Methods: Using iodine-123-N-isopropyl-p-iodoamphetamine single-photon emission computed tomography (IMP-SPECT), we performed a cross-sectional study of 44 patients with diabetes, and compared CBF in those with (n = 24) and without neuropathic pain (n = 20). In patients with neuropathic pain, we also longitudinally assessed changes in CBF 3 months after treatment with duloxetine. Results: IMP-SPECT with voxel-based analyses showed a significant increase in cerebral blood flow in the right anterior cingulate cortex and a decrease in the left ventral striatum in patients with neuropathic pain, compared with those without pain. After duloxetine treatment, volume of interest analyses revealed a decrease in cerebral blood flow in the anterior cingulate cortex in patients with significant pain relief but not in non-responders. Furthermore, voxel-based whole brain correlation analyses demonstrated that greater baseline CBF in the anterior cingulate cortex was associated with better pain relief on the numerical rating scale. Conclusions: Our results suggest that the development of neuropathic pain is associated with increased activity in the anterior cingulate cortex, and greater baseline activation of this region may predict treatment responsiveness to pharmacological intervention. Trial registration number: UMIN000017130;Results.